Eye Health Screening in School-Age Children During Online Learning - Riri Novayelinda; Oswati Hasanah (Journal Kiara : Nursing and Midwifery, 2025)
The "school from home" policy during the COVID-19 pandemic a few years ago led to increased interaction between children and gadgets. Prolonged and intense gadget use among children can result in complaints that, if left unaddressed, may cause vision problems. To prevent permanent eye damage, it is essential to conduct vision screening for school-aged children to identify potential issues. This study was conducted in 2020 using a simple descriptive method with accidental sampling, involving 50 children aged 8–13 years as research respondents. Vision screening using the PEEK Acuity application revealed that 52% (26 children) had abnormal visual acuity. Additionally, 46% (23 children) reported symptoms of dry eye, such as frequent eye rubbing. Furthermore, 72% of the children used gadgets for more than 2 hours per day. The study concludes that nearly half of the children had undetected visual acuity issues. Regular eye examinations for school-aged children are recommended to identify eye problems as early as possible.